Formação e capacitação profissional no setor hoteleiro de Ponta Negra, Natal/RN: turismo e políticas públicas - Maia, Severino Ramos dos Santos (2005)
This paper aims to analyse and discuss the labour in hospitality industry, specially the hospitality trade in Ponta Negra Natal/RN, Brazil, since the tourism has increased in the city, by investigating if the tourism field is suitable for public politics programs and labour qualification. The choice for Ponta Negra is because it has become the focus of tourism development in Natal. The research was developed by using qualitative approach of investigation, by means of some procedures such as: bibliographic and empirical researches, by using questionnaires with workers and recruiting personnel of hotels, always following a theory and a reflexive descriptive attitude. This dissertation involves eight chapters: Neoliberalism and labour; Economical and spatial restructuring of Rio Grande do Norte; Public politics concerning tourism area; Tourism, graduation and qualification in hospitality industry; Qualification for tourism hospitality; Hotels: territorialization and unterritorialization; Social qualification reality of people involved in hospitality activities in Ponta Negra, Natal/RN, Brazil; and Final considerations and recommendations. Therefore, this paper intends to contribute for understanding professional qualification in hospitality trade, confronting the needs that the service requires, and mainly, in the tourism sector, which is increasing in our city, Natal